A Review of Super plastic forming. (2018) - Chatterjee, Ritam; Mukhopadhyay, Jyoti
Abstract: Super plasticity is the property exhibited by a few metals and alloys which involves, under tensile loading, very high elongation without necking until failure. This was first closely studied by Back ofen, Turner and Avery at MIT in 1964 [1]. Their pioneering work has since given rise to the multi-million dollar superplastic forming industry which has been highly successful in fabrication of complex shaped components mainly for the aerospace and automobile industries. The present paper reviews the developments related to superplastic forming that has taken place mainly over the past two decades. The process parameters, underlying mechanisms, constitutive equations and the process economics have been discussed in details. Furthermore, there is a brief discussion about quick-plastic forming which is an upcoming metal forming technique that promises to replace superplastic forming in the near future. This is largely due to the faster forming times associated with quick-plastic forming as compared to superplastic forming.